2016
DOI: 10.3109/10799893.2015.1132237
|View full text |Cite
|
Sign up to set email alerts
|

Structural insights on identification of potential lead compounds targeting WbpP inVibrio vulnificusthrough structure-based approaches

Abstract: WbpP encoding UDP-GlcNAC C4 epimerase is responsible for the activation of virulence factor in marine pathogen Vibrio vulnificus (V. vulnificus) and it is linked to many aquatic diseases, thus making it a potential therapeutic target. There are few reported compounds that include several natural products and synthetic compounds targeting Vibrio sp, but specific inhibitor targeting WbpP are unavailable. Here, we performed structure-based virtual screening using chemical libraries such as Binding, TOSLab and May… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The model has ≥90% of the amino acid residues present in allowed regions represents a good quality model. Similar protocols were followed as reported recently in drug discovery process and lead identification [66][67][68]. The UBE2D4 model has 91.9% of the amino acid residues present in the allowed regions, and hence, it is a good quality model.…”
Section: Ube2d4 Protein Modelling and Validationmentioning
confidence: 96%
“…The model has ≥90% of the amino acid residues present in allowed regions represents a good quality model. Similar protocols were followed as reported recently in drug discovery process and lead identification [66][67][68]. The UBE2D4 model has 91.9% of the amino acid residues present in the allowed regions, and hence, it is a good quality model.…”
Section: Ube2d4 Protein Modelling and Validationmentioning
confidence: 96%
“…Sasikala et al also conducted a virtual screen of RmlC and identified several potential inhibitors of the Vibrio vulnificus enzyme (also known as WbpP). 261 However, none of these compounds were confirmed as hits in biochemical or biophysical screens.…”
Section: Inhibitors Of Racemases and Epimerasesmentioning
confidence: 99%
“…[258][259][260] RmlC is also responsible for activation of the virulence factor in the marine pathogen Vibrio vulnificus. 261 Several inhibitors of RmlC have been previously characterised (including the high-throughput screening inhibitors noted above; 228 vide supra, Fig. 16), although many have limited aqueous solubility.…”
Section: Cofactor-independent Racemases and Epimerasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Three-dimensional (3D) crystal structures or homology models of the Vibrio-speci c targets reported in recent years on RCSB Protein Data Bank (PDB) or UniProt Database were used for molecular docking (Bonardi et Sasikala et al 2016). The AutoDock Tools 1.5.6 software was used to remove the water molecules, add the nonpolar hydrogen, and calculate the Gasteiger charges for the protein structures.…”
Section: Molecular Dockingmentioning
confidence: 99%